Estimasi Jarak Dan Waktu Bus Sekolah Pada System Pemetaan Trayek Bus Sekolah Dan Halte Di Central Business District (CBD) Bangkinang - Emi Khoiriyatun; Novi Yona Sidratul Munti; Deddy Gusman (Universitas Pahlawan Tuanku Tambusai, 2021)
Information about estimated distance and time on school buses is very useful for students and educators because these students and educators can find out what time the bus will arrive at the bus stop and how long the bus will take to reach the location. This bus is usually used to transport students and educators to and from school. The Kampar Regency Transportation Agency has 5 operating school buses. This school bus operates according to their respective bus routes, however, the lack of information obtained by the community and students, so that there are still many educators and students who do not know the schedule of the school bus. For this reason, it is necessary to estimate the distance and time of school buses used to map school bus routes and bus stops in the Bangkinang Central Business District (CBD), which can be used by students, educators and the community to obtain information about school buses and bus stops in Central Bangkinang Business District (CBD). The purpose of this researcher is to know the estimated distance and time so that it can make it easier for students and educators who want to use school buses. The system designed is a web-based system as a medium to provide information to the public. The programming languages used are HTML, PHP, and Mysql as databases which are expected to make it easier for admins to manage data efficiently.